(untitled) (Research, Society and Development, 2021)
The worker’s health is an area of public health that aims to analyze and intervene on work relations that result in diseases and diseases contributing to the improvement of the quality of life. To analyze the prevalence of health professionals who suffered work-related injuries in the state of Rio Grande do Norte. Methodology: Cross-sectional study of prevalence, which had as inclusion criteria diseases/occupational health in the following professional categories: Physician, Dental Surgeon, Nurse, Nursing Technician and Oral Health Assistant. As an exclusion criterion, no information was included that would compromise the personal integrity of victims of accidents at work. Results and Discussion: As a result, it was pointed out that the nursing technician is responsible for the majority of cases in all work-related diseases reported in the state of Rio Grande do Norte. The most reported problem in this research, between 2008 and 2018, was exposure to biological material, with 98%, followed by serious work accident, with 1% and mental disorder, with 1%. It was also found that the frequency of notifications has been increasing over the years. These results show the need for greater awareness of the work process and preventive activities, since the worker’s health is an important axis of public health. Conclusions: It is concluded that there is a significant prevalence of occupational accidents involving health professionals, evidencing that there is a failure in the performance of their functions, possibly because they do not use simple prevention protocols. Therefore, it is recommended that health professionals in Rio Grande do Norte expand their awareness of their work process, acquiring scientific knowledge to prevent health problems.